Two strategies to improve stability in a precision-based task: Insights from the badminton short serve - Iino, Y.; Wilkie, J. C.; Fukashiro, S.; Yoshioka, S.; Vial, S. (Journal of Biomechanics, 2025)
The badminton short serve is a highly precise task requiring accurate control of racquet face orientation, which directly influences shuttlecock trajectory and limits an opponent`s ability to attack. Previous studies on motor redundancy have emphasized covariation among elemental variables as the primary mechanism for stabilizing performance. However, when the sensitivities of elemental variables differ, performance can also be stabilized by unevenly distributing individual variances without altering correlation — an approach that has received limited attention. This study investigated whether elite players use both the correlation strategy and the uneven variance strategy to stabilize racquet face angles during the short serve. Motion capture data were collected from eight elite players, and permutation and bootstrapping methods assessed the contribution of each strategy based on two covariance representation. At the group level, players employed the correlation strategy to stabilize the vertical racquet face angle throughout the swing (effect size = 3.24) but did not use the uneven variance strategy. In contrast, both strategies were observed for the horizontal angle at impact, showing large effect sizes of 1.61 for correlation and 1.28 for uneven variance. The results suggest that uneven variance allocation can act as a complementary strategy, selectively stabilizing the subtask less supported by correlations. These findings underscore the importance of considering both strategies in motor tasks where the sensitivities to elemental variables are not uniform. Joint angle variability and correlation patterns were individualized, indicating that understanding their structure in each player can inform personalized training approaches to improve stability in precision-oriented movements.